1998
DOI: 10.1073/pnas.95.21.12550
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 18 stimulates HIV type 1 in monocytic cells

Abstract: The cytokine interleukin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
3
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 47 publications
3
82
3
2
Order By: Relevance
“…Although an early report suggested that IL-18 increased human immunodeficiency virus (HIV)-1 production in a chronically infected monocytic cell line [111], recent studies predict a protective role with IL-18 inhibiting HIV-1 production by peripheral blood cells [112]. In vaccine studies, the coinjection of DNA encoding IL-18 modulates the specific immune response toward a protective Th1 type [113].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Although an early report suggested that IL-18 increased human immunodeficiency virus (HIV)-1 production in a chronically infected monocytic cell line [111], recent studies predict a protective role with IL-18 inhibiting HIV-1 production by peripheral blood cells [112]. In vaccine studies, the coinjection of DNA encoding IL-18 modulates the specific immune response toward a protective Th1 type [113].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Similar effects were observed in other viral mouse models 23,24 . Interestingly, in a monocytic cell line, IL-18 stimulated HIV replication 25 .…”
Section: Relationships Between Treatment Response and The Il-18 Genementioning
confidence: 99%
“…Because IL-18 was reported to induce NF B activation (Matsumoto et al, 1997;Shapiro et al, 1998;Torigoe et al, 1997), we investigated whether this transcription factor was involved in the IL-18 -induced IL-8 expression. When NF B is activated, it translocates from the cytoplasm to the nucleus.…”
Section: Il-18 Induces Nuclear Translocation Of Nf B (P65) In Ra Synomentioning
confidence: 99%